Radiofrequency ablation versus resection for the treatment of early stage hepatocellular carcinoma: a multicenter Australian study. (May 2014) - Gory, Ilana; Fink, Michael; Bell, Sally; Gow, Paul; Nicoll, Amanda; Knight, Virginia; Dev, Anouk; Rode, Anthony; Bailey, Michael; Cheung, Wa; Kemp, William; Roberts, Stuart K.
Abstract Objectives. It remains unclear whether radiofrequency ablation (RFA) provides comparable outcomes to surgical resection (SR). We, therefore, compared survival outcomes of RFA to SR in patients with early stage and very early stage hepatocellular carcinoma (HCC). Methods. A multicenter retrospective analysis was performed in patients from five academic hospitals with Barcelona Cancer of the Liver Clinic (BCLC) stages 0–A HCC having RFA or SR as primary therapy. Results. From 2000–2010, 146 patients who received treatment with RFA (n = 96) or SR (n = 52) were identified. In BCLC A patients with ≤5 cm HCC, there was a trend of lower overall survival after RFA compared with SR (3- and 5-year survival: 62% and 37% vs. 66% and 62% respectively; p = 0.11). By multivariate analysis, RFA was an independent predictor of poor survival (hazard ratio = 2.26; 95% confidence interval: 1.02–5.03; p = 0.04). In ≤3 cm HCC (n = 109), the 3- and 5-year survivals in RFA and SR groups were 66% and 39%, and 69% and 59%, respectively, with no difference in the median survival (p = 0.41). Local recurrence was significantly higher after RFA compared to SR in HCC ≤5 cm (p = 0.006) with a trend of lower recurrence-free survival (p = 0.06) after RFA in HCC ≤3 cm. There were fewer major complications after RFA (2% vs. 8%). Conclusion. While SR is superior to RFA for the management of early stage BCLC A disease with ≤5 cm HCC, both appear effective as first-line treatment options for Western patients with small ≤3 cm tumors. Although safer than SR, RFA is associated with higher rates of tumor recurrence and local disease progression. Further prospective randomized controlled trials are warranted to compare these two modalities.